Efeito do fogo na organização espacial e dinâmica em uma floresta tropical - Silva, Kmila Gomes da (2017)
The objectives of this study were 1) to characterize the distribution pattern and spatial dependence of the species diversity without forest fragment after incidence of fire and 2) identify temporal patterns in the tree community and characterize its structure and global dynamics over time. A semideciduous seasonal forest fragment was struck by fire in 1999 and in 2000, 2005, and 2014, inventories in 26 plots of 400 m 2 were carried out, georeferenced, and distributed into two sectors (Valey and Slope). The fire damage index (FDI) in each plot was evaluated based on a score from 0 to 5. In each inventory, all tree individuals with a diameter at breast height (DBH) ≥ 5 cm were identified, the species diversity was calculated on the basis of the Shannon index (H'), and the species richness (S) was measured. These variables were analyzed using the species accumulation curve; then the S, H’, and FDI data were subjected to nonspatial exploratory and geostatistical analyses. In the dynamics study, the structural and dynamics descriptor parameters, besides the diametric structure and regeneration guilds, were quantified for the total sampling and for the two sectors. The variables S and H’ presented spatial dependence and aggregate distribution pattern, with spatial continuity reduced throughout the inventories. There was oscillation in the number of individuals and increase in the basal area during the inventories. The mortality rate decreased, while the recruitment rate increased between the periods (2000-2005 and 2005-2014). On the other hand, the gain rate in basal area exceeded the loss rate. The changes in the parameters of total sample (community) characterize a post-fire recovery phase. The high recruitment followed by the growth of individuals in the larger -size classes characterizes the Slope sector as resilient when compared to the Valey. On the other hand, the substitution of pioneer species for light-demanding climax and shadow-tolerant species in the Valey indicates advance in succession. Changes in structure and recruitment of tree individuals still occur in the forest 15 years after the disturbance.